2012
DOI: 10.1039/c2jm16650j
|View full text |Cite
|
Sign up to set email alerts
|

Transition between widened BPs by light irradiation using photo-active bent-core liquid crystal with chiral dopant

Abstract: Upon UV irradiation of a bent-core liquid crystal (LC) bearing an azo linkage doped with chiral molecules, a photo-induced transition takes place from BPI to BPIII. BPIII is stabilised over 20 C, while the widening of the BPI range is not so remarkable. The mechanism of photo-induced BPI-BPIII transition is also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Additionally, the cis-to-trans back-isomerization can be accelerated by exposure to green light. Similar isomerization-induced range expansion had also been discovered [51].…”
Section: Expansion Of Temperature Range Of Bpsmentioning
confidence: 82%
See 2 more Smart Citations
“…Additionally, the cis-to-trans back-isomerization can be accelerated by exposure to green light. Similar isomerization-induced range expansion had also been discovered [51].…”
Section: Expansion Of Temperature Range Of Bpsmentioning
confidence: 82%
“…In most cases, cubic BPs can simply be recognized by the appearance of colored platelets under polarizing optical microscope (POM) [40], while BPIII, the fog-like phase, shows extremely weak reflection and scattering, which makes its identification relatively hard [51]. Precise phase identification of cubic BPs is often carried out in conjunction with certain supplementary approaches like Kössel diagram and reflection/transmission spectrum.…”
Section: Phase Identification Of Bpmentioning
confidence: 99%
See 1 more Smart Citation
“…Achiral bent-core dopants were also used for BP stabilization as polymers and nanoparticles did [213], and the phase temperature range was greatly widened. Jeong et al [214] reported that UV irradiation of an azo-benzene bent-core LC doped with chiral molecules leads to a photo-induced transition from BPI to BPIII, accompanied by BPIII stabilization of 20 • C. Many papers dealing with BPs and bent-core molecules have been published [215][216][217][218][219]. How to achieve uniform alignment might be still an important issue to consider for bent-core BP viable applications.…”
Section: Othersmentioning
confidence: 99%
“…16 Since then, some other bent shaped molecules containing azobenzene moieties have been synthesized, the majority of these molecules presenting interesting liquid crystalline properties. [16][17][18][19][20][21][22][23][24] The goal of the paper is to extent the classes of bent shaped molecules containing the azo photoisomerisable group. The paper presents the synthesis of some bent-core liquid crystals based on a 1,3-dihydroxy-benzene core with two symmetric wings containing each three benzene rings connected via esteric, azomethinic and azo groups.…”
Section: Introductionmentioning
confidence: 99%